Challenges in Service Provision to Children and Families from Linguistically Diverse Backgrounds - Fumero, Keisey; Torres-Chavarro, Michelle; Wood, Carla (Seminars in Speech and Language, 2021)
The purpose of this study was to examine and describe experiences and perceptions of speech-language pathologists (SLPs) serving children and families from culturally and linguistically diverse populations. Twenty SLPs were interviewed using an online audio platform regarding common practices, resources and supports, challenges, and communication. Participants' responses to the semi-structured questions were transcribed and analyzed to identify themes in experiences. Results suggested six overall themes including: considerations for assessment; cultural impact; linguistic access and barriers; professional preparedness; impact of COVID-19; and helpful tips and resources. The discussion includes recommendations and resources to address obstacles.
Keywords: bilingual; intervention; family-centered services; assessment